The influence of legislative oversight on discretionary authority: allocating urban development action grants in HUD's office of community planning and development - Duffin, Diane L. (1999)
Theories suggest that administrators may use their discretion to advance their agency's version of the public interest, court political support, or both. The author hypothesizes that administrators courting political support use their discretion to reward legislators who monitor their programs more closely than do other legislators. The author measures the degree of scrutiny a program receives by quantifying members' participation in oversight hearings. In analyzing the allocation of Urban Development Action Grants (UDAGs), the author finds that administrators in the U.S. Department of Housing and Urban Development's (HUD) Office of Community Planning and Development were guided by both the agency's perception of the public interest and by political considerations. Members of the House Committee on Banking, Finance and Urban Affairs who participated more extensively in hearings overseeing HUD programs received larger UDAG allocations in their home districts, and more oversight led to more grant money. - Reproduced
Keywords: Community development